Do additional sugar sources affect the degree of attendance of Dysmicoccus brevipes by the fire ant Solenopsis geminata? - Carabalí-Banguero, D.J.; Wyckhuys, Kris A.G.; Montoya Lerma, J.; Kondo, T; Lundgren, Jonathan G. (Wiley, 2013)
Mutualistic interactions between ants and Hemiptera are mediated to a large extent by the amount and quality of sugar‐rich honeydew produced. Throughout the neotropics, the predaceous fire ant Solenopsis geminata (Fabricius) (Hymenoptera: Formicidae) is found in association with colonies of the pineapple mealybug, Dysmicoccus brevipes (Cockerell) (Hemiptera: Pseudococcidae), which they actively tend and protect from attack by natural enemies. In this study, we evaluate the effects of access to a sucrose solution on the mutualistic association between S. geminata and D. brevipes. Ten colonies of either species were established, with D. brevipes maintained on pumpkin, Cucurbita maxima Duchesne (Cucurbitaceae), in screen cages. Five of the S. geminata colonies were permitted access to vials with 20% sucrose solution and a pumpkin with 20 adult mealybugs. The remaining ant colonies were allowed access to mealybug‐infested pumpkins. Ant colonies with access to the sucrose solution attended mealybugs significantly less than those without additional sugar sources. Mealybug survival rates were similar under both treatments. Total body sugars and fructose were nearly twice as high in ants with access to honeydew and sucrose vs. those with access to honeydew and water. Fructose accumulated on the pumpkins over time in both treatments, suggesting that honeydew was not fully exploited by the ants. In conclusion, D. brevipes enjoy lower degrees of ant attendance when S. geminata have alternative sources of carbohydrates. We further discuss the significance of these findings for the conservation of predaceous ants and mealybug biological control.